Hunter killer : the war with China - the battle for the Central Pacific - Poyer, David (Poyer, David. Tales of the modern Navy., 2017)
"The United States stands nearly alone in its determination to fight, rather than give into the expansionist demands of the aggressive new "People's Empire." The naval and air forces of the Associated Powers - China, Pakistan, Iran, and North Korea - have used advanced technology and tactical nuclear weapons to devastate America's fleet in the Pacific, while its massive army forced humiliating surrenders on Japan, Taiwan, the Philippines, and other crucial allies ..."--